2019
DOI: 10.1016/j.jgo.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Use of a comprehensive frailty assessment to predict morbidity in patients with multiple myeloma undergoing transplant

Abstract: Our data illustrate that a GA can identify individuals with MM who are at greater risk for morbidity following ASCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 46 publications
1
51
0
2
Order By: Relevance
“…Furthermore, many older adults are frail and have functional, psychological, and social vulnerabilities that may affect how information is communicated and processed. These age‐related vulnerabilities are associated with higher morbidity and mortality and add complexities to the care of and treatment decisions among older adults with cancer. Older adults are at a higher risk of experiencing adverse events related to cancer treatments ; therefore, ensuring older adults have similar beliefs about curability as their oncologists may allow them to receive goal‐concordant care.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many older adults are frail and have functional, psychological, and social vulnerabilities that may affect how information is communicated and processed. These age‐related vulnerabilities are associated with higher morbidity and mortality and add complexities to the care of and treatment decisions among older adults with cancer. Older adults are at a higher risk of experiencing adverse events related to cancer treatments ; therefore, ensuring older adults have similar beliefs about curability as their oncologists may allow them to receive goal‐concordant care.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing age-related deficits prior to autologous HCT is important to minimize morbidity and mortality among older adults and maximize quality of life following HCT. Impairment in pre-transplant physical function is associated with longer HCT-CI (p = 0.02) − Age (HR 1.084, p = 0.0011) − HCT-CI (HR 1.129, p = 0.048) − ADL change a (HR 0.989, p = 0.011) − IADL change a (HR 0.83, p b 0.0001) − Nutrition (HR 0.865, p = 0.0063) − Nutrition status change (HR 0.894, p = 0.0007) − Age b (HR 1.08, p = 0.002) − KPS b (HR 0.97, p = 0.02) − TUG (HR 3.26, 95% CI 1.001-10.6, p = 0.049) − Fatigue (HR 1.09, p = 0.039) − ADL change a (HR 0.986, p = 0.0021) − IADL change a (HR 0.849, p = 0.0014) − KPS change (HR 0.961, p b 0.0001) − Nutrition (HR 0.878, p = 0.0198) − Age (≥ 60; p = 0.0005) − IADL (p = 0.0003) − HCT-CI (p = 0.03) Not reported − Age (≥60; p = 0.0007) − IADL b (p b 0.0001) − HCT-CI (p = 0.03) − Mental health b (p = 0.01) − Walk speed b (p = 0.009) hospitalization, and weight loss pre-transplant correlates with higher relapse and death post-transplant in an age unrestricted study of adults with multiple myeloma [72]. This study also found a number of geriatric domains to be predictive of re-admissions: mental health, physical function, nutrition.…”
Section: Autologous Hctmentioning
confidence: 99%
“…Although of considerable interest, only limited data exists to date on GA after HCT. In patients age ≥18, GA three months after autologous HCT uncovered less fatigue but worse physical function [72]. Deschler et al performed GA in patients age ≥60 at one, three, and six months after allogeneic HCT [64].…”
Section: Post-hctmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, low physical pre-transplant function and weight loss are associated with longer transplant hospitalizations. 25 The CARE clinic assesses older adult transplant candidates as well as younger patients for whom the referring provider has specific concerns. The CARE clinic uses a standardized GA, Rockwood's clinical frailty scale, 26 and the 1-year overall Center for International Blood and Marrow Transplant Research survival calculator 27,28 The CARE clinic's primary goal in evaluating transplant candidates is to identify deficits and mitigate risk factors to improve tolerability of the transplant.…”
Section: Hematologic Malignanciesmentioning
confidence: 99%